Theoretical Study of the Steady Time of Thermal Transmission in Materials That Have Engineering Uses: Studi Teoritis tentang Waktu Tenang Transmisi Termal pada Material yang Memiliki Kegunaan Teknik - AlAttar, Raghad Hikmet; Allawy, Asim S.; Dakkama, Hassan. J (Procedia of Engineering and Life Science, 2024)
General Background: Understanding the time required to achieve steady-state heat transfer in construction materials is crucial for various engineering applications, including construction, architecture, and electronics. Specific Background: This study investigates the steady time of thermal transmission in engineering materials using both theoretical and experimental approaches. Knowledge Gap: Despite existing research on heat transfer, there is a lack of comprehensive studies that integrate both simulation and experimental validation for a wide range of building materials.Aims: The primary aim is to evaluate the steady-state time of heat transfer in fifteen construction materials through theoretical models and simulations using MATLAB and ANSYS, and to experimentally validate these findings with four selected materials. Results: The study finds that the steady time for heat transfer varies significantly among materials, with wood packaging requiring the longest time (32.49 hours) and aluminum the shortest (0.49 hours). Theoretical results, validated by simulations, show close agreement between MATLAB and ANSYS (0.087% deviation) and between numerical and experimental results (9.5% deviation). Brick demonstrated a 61.18% longer heat transfer time compared to concrete, while thermostone showed a 17.45% and 89.31% increase over brick and concrete, respectively. Novelty: This research provides new insights into the comparative stability of heat transfer times across a broad spectrum of materials, highlighting significant performance variations and validating simulation methods against experimental data. Implications: These findings are vital for optimizing material selection in construction to enhance thermal efficiency. The study’s methodologies can aid in developing more accurate predictive models for heat transfer in construction materials, thereby contributing to improved design and energy performance in building applications.